Wisconsin - Franchino, Vicky (New York, Children's Press, 2018)
An introduction to the wildlife, history, and culture of Wisconsin.
Land and wildlife -- Government -- History -- Culture.
Includes bibliographical references (page 46) and index.
6.7
3-6
890L
Keywords: Wisconsin -- Juvenile literature; Wisconsin